Labour relations: a conflict trap - Ferris, Frank D
Using the techniques of conflict analysis, this article looks at Title VII of the Civil Service Reform Act (CSRA) which regulates the labour-management relationship between federal employees and their managers. The Act's techniques for managing conflict are high lighted analyzed, and then compared to alternative ways of managing conflict to see if the costs can be lowered and the benefits raised
Keywords: Management; Conflict Management; Labour Relations